2021
DOI: 10.3390/microorganisms9051026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lacticaseibacillus paracasei Strain Shirota on Improvement in Depressive Symptoms, and Its Association with Abundance of Actinobacteria in Gut Microbiota

Abstract: We previously reported lower counts of lactobacilli and Bifidobacterium in the gut microbiota of patients with major depressive disorder (MDD), compared with healthy controls. This prompted us to investigate the possible efficacy of a probiotic strain, Lacticaseibacillus paracasei strain Shirota (LcS; basonym, Lactobacillus casei strain Shirota; daily intake of 8.0 × 1010 colony-forming units), in alleviating depressive symptoms. A single-arm trial was conducted on 18 eligible patients with MDD or bipolar diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…In a subgroup with a high depressive index at baseline, intervention subjects showed a significant improvement in depressive mood compared with subjects who received a placebo control. These results were supported by those from an open trial using the same probiotic strain in patients with MDD or bipolar disorder [130]. There, it was demonstrated that depressive symptoms and sleep quality were improved after LcS treatment, and the effect was associated with the gut microbiota composition, namely, abundance of Actinobacteria, including Bifidobacterium.…”
Section: Ameliorating the Stress Responsementioning
confidence: 53%
“…In a subgroup with a high depressive index at baseline, intervention subjects showed a significant improvement in depressive mood compared with subjects who received a placebo control. These results were supported by those from an open trial using the same probiotic strain in patients with MDD or bipolar disorder [130]. There, it was demonstrated that depressive symptoms and sleep quality were improved after LcS treatment, and the effect was associated with the gut microbiota composition, namely, abundance of Actinobacteria, including Bifidobacterium.…”
Section: Ameliorating the Stress Responsementioning
confidence: 53%
“…L. paracasei can be commonly found as the dominant nonstarter lactic acid bacterium in many ripened cheeses, and select strains of this species may be added to cheese milk as adjuncts for outcompeting undesired microorganisms and improving cheese quality by contributing to cheese flavor diversification and intensification [36]. Moreover, the probiotic properties of L. paracasei have been investigated in recent studies [37]. Other facultative heterofermentative NSLAB detected in very low populations were Lacticaseibacillus casei (former Lactobacillus casei), Latilactobacillus graminis (former Lactobacillus graminis), Latilactobacillus sakei (former Lactobacillus sakei) and Lacticaseibacillus zeae (former Lactobacillus zeae).…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the gut microbiota composition prior to and after the probiotic supplementation provides important information about the gut microbiome and its influence on depressive disorders. Otaka et al [ 87 ] used Lacticaseibacillus paracasei strain Shirota. The researchers found the link between the reduction in depressive symptoms and the gut microbiome.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers found the link between the reduction in depressive symptoms and the gut microbiome. Reduced symptoms of depression were partially related to the increase in Actinobacteria in the gut microbiome [ 87 ]. Most of the studies illustrated by us showed a positive effect on depressive behavior among patients.…”
Section: Resultsmentioning
confidence: 99%